2019
DOI: 10.5219/1144
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical study of steroids from different matureness corn silk material

Abstract: This study shows an ultrasonic assisted extraction procedure of steroids from corn silk (CS). The total steroids contents were positively correlated with the ultrasonic assisted extraction time. The extracted steroids contents varied according to the different maturity stages of CS. There were three tested CS maturity stages: silking stage (CS-S), milky stage (CS-M) and mature stage (CS-MS). The β - sitosterol standardization method with 530 nm wavelength colorimetric measurements were applied to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…In the range of 60-75 min, a slight increase in steroids content was detected. Therefore, 75 min of ultrasonication at laboratory temperature may be defined as the optimal extraction time to gain the maximum steroids content for all CS maturity stages under study, as also confirmed in our previous study [38]. The CS-MS sample yielded the highest steroid concentration (0.37 mg/mL) accompanied with the increased extraction rate via ultrasonic treatment compared to the CS-M sample (0.12 mg/mL) and CS-S (0.09 mg/mL).…”
Section: Corn Silk Steroids Extraction and Determinationsupporting
confidence: 66%
See 2 more Smart Citations
“…In the range of 60-75 min, a slight increase in steroids content was detected. Therefore, 75 min of ultrasonication at laboratory temperature may be defined as the optimal extraction time to gain the maximum steroids content for all CS maturity stages under study, as also confirmed in our previous study [38]. The CS-MS sample yielded the highest steroid concentration (0.37 mg/mL) accompanied with the increased extraction rate via ultrasonic treatment compared to the CS-M sample (0.12 mg/mL) and CS-S (0.09 mg/mL).…”
Section: Corn Silk Steroids Extraction and Determinationsupporting
confidence: 66%
“…Steroids extraction kinetics was characterized as a non-linear third-order polynomial dependency [38]. However, there was a proportional trend between corn silk steroid concentration and ultrasonic processing time from 15 to 60 min.…”
Section: Corn Silk Steroids Extraction and Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysing the vitamin composition of whole-ground corn flour in comparison with first-grade wheat flour, it can be concluded that corn flour is rich in vitamins [47], [48], [49]. In particular, the content of niacin (vitamin PP) in corn flour is 1.54 times higher than in wheat flour.…”
Section: Discussionmentioning
confidence: 99%